CLASSROOM MANAGEMENT OF LEARNING ACTIVITIES AT MADRASAH; EXPLORING THE MEANING OF THE TEACHER'S ROLE - Mas'udi, Ahmad Thoyib (Universitas Nurul Jadid, 2022)
This study aims to analyze and understand the meaning of classroom management for Islamic Religious Education teachers at Madrasah Aliyah Ihyaul Ulum. Researchers use a qualitative approach to the type of case study. Data collection techniques are carried out through observation, interview, and documentation. Research results show that; Class management is understood as a form of the central role and duties of an Islamic religious teacher, which must be carried out thoughtfully and responsibly. Second, the implementation of class management in Islamic Religious Education learning is motivated by the teacher's desire to achieve his learning goals in Madrasahs. Third, implementing class management in learning Islamic Religious Education aims to improve the quality of learning. Fourth, creating a comfortable learning atmosphere for learning Islamic Religious Education.